2013
DOI: 10.17503/agrivita-2013-35-1-p095-102
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield Stability of Sweet Potato Clones across Four Locations in East Nusa Tenggara

Abstract: A number of promising sweet potato clones from East Nusa Tenggara and a checked cultivar were evaluated in several locations for the following objectives: 1) to elucidate genotype by environment effect on growth and yield of the sweet potato clones, and 2) to determine growth and yield stability of the clones across diverse locations in East Nusa Tenggara province. The study was carried out in four locations and was laid out in a Randomized Block Design consisting of 10 sweet potato genotypes as treatments and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
2
7
1
1
Order By: Relevance
“…The F 1 clones UNC2016.Cil/JPV.04 and UNC2016.KDL/V1.CIL.01, respectively, showed the highest and the lowest number of secondary branches per plant, ranging from 5.7 to 11.5 branches per plant. Number of secondary branches per plant of the current study was not substantially different from that in orange-fleshed sweet potato observed by Rahman et al (2013) but the range was much wider than that found in local sweet potato of NTT Province (5-6 branches per plant) (Mau et al 2013) and the ILETRI germplasm collection (0.3-1.5 branches per plant) (Rahajeng and Rahayuningsih 2017a). The wider range of secondary branches per plant of the present study may indicate that the sweet potato genotypes evaluated possess a higher genetic diversity of the trait.…”
Section: Growth Variablescontrasting
confidence: 60%
See 4 more Smart Citations
“…The F 1 clones UNC2016.Cil/JPV.04 and UNC2016.KDL/V1.CIL.01, respectively, showed the highest and the lowest number of secondary branches per plant, ranging from 5.7 to 11.5 branches per plant. Number of secondary branches per plant of the current study was not substantially different from that in orange-fleshed sweet potato observed by Rahman et al (2013) but the range was much wider than that found in local sweet potato of NTT Province (5-6 branches per plant) (Mau et al 2013) and the ILETRI germplasm collection (0.3-1.5 branches per plant) (Rahajeng and Rahayuningsih 2017a). The wider range of secondary branches per plant of the present study may indicate that the sweet potato genotypes evaluated possess a higher genetic diversity of the trait.…”
Section: Growth Variablescontrasting
confidence: 60%
“…Vine length varied considerably from 55.7 cm (BETA-2) to 149 cm (UNC2016.PSOL/NPL.15) while leaf number per plant ranged from 160 (UNC2016.KDL/V1.CIL.01) to 368 (UNC2016.JPV/KDL.11). Most of the clones had a short to moderate vine length, much shorter than those observed in orange-fleshed sweet potato (117.3-253.3 cm) reported by Rahman et al (2013) and local sweet potatoes from NTT Province (115.9-216.4 cm) (Mau et al 2013). In contrast to vine length, leaf number per plant of the present study (160.3-366.5) was much higher (about three folds) than that observed in the local sweet potato from NTT Province (50.8-127.3 cm) (Mau et al 2013).…”
Section: Growth Variablesmentioning
confidence: 58%
See 3 more Smart Citations